Peran Quality of Work Life terhadap Turnover Intention pada Karyawan Generasi Z di Startup - Okta Trianda; Pundani Eki Pratiwi (Universitas Muhammadiyah Metro, 2026)
Turnover intention among Generation Z employees has become an increasingly critical phenomenon, especially given the fast-paced work dynamics and high job demands in startup companies. This study aims to examine the role of quality of work life in influencing turnover intention among Generation Z employees in Indonesian startups. Employing a quantitative correlational associative design, the research involved 335 participants selected through purposive sampling. Participants were employees aged 18–28 years, working in startups in Indonesia with a minimum tenure of six months. Data were collected using the Quality of Working Life (QWL) Scale and the Turnover Intention Scale (TIS-6). Data analysis was conducted using simple linear regression with JAMOVI 2.3.28 software. The findings indicate that quality of work life significantly affects turnover intention among Generation Z employees in startups. Among the dimensions assessed, competency development scored the highest mean, while work and non-work life balance scored the lowest. Although the contribution of quality of work life to turnover intention was moderate (R² = 0.139), these results highlight the important role of quality of work life in reducing turnover intention in this demographic and context. Practically, startup companies are advised to focus on enhancing aspects of quality of work life, particularly work and non-work life balance, as a strategic measure to mitigate turnover intention among Generation Z employees.